Efficacy decrease of antiviral agents when administered to ongoing hepatitis C virus infections in cell culture - García-Crespo, Carlos; Vázquez-Sirvent, Lucía; Somovilla, Pilar; Soria, María Eugenia; Gallego, Isabel; de Ávila, Ana Isabel; Martínez-González, Brenda; Durán-Pastor, Antoni; Domingo, Esteban; Perales, Celia (Frontiers in Microbiology, 2022)
We report a quantification of the decrease of effectiveness of antiviral agents directed to hepatitis C virus, when the agents are added during an ongoing infection in cell culture. Major determinants of the decrease of inhibitory activity are the time post-infection of inhibitor administration, and viral replicative fitness. The efficacy decrease has been documented with antiviral assays involving the combination of the direct acting antiviral agents daclatasvir and sofosbuvir, as well as the combination of the lethal mutagens favipiravir and ribavirin. The results suggest that strict antiviral effectiveness assays in preclinical trials should involve the use of high fitness virus populations, and the delayed administration of the agents, relative to infection onset.